Marriage In Islam and the Problem of Gender Equality: A Philosophical Perspective - Mudofir Abdullah (Ulumuna, 2018)
Marriage law in Islamic countries is still considered gender-biased. Indonesia, as the majority Muslim country, is not exception. Marriage Law No. 1/1974 and the Compilation of Islamic Law (Kompilasi Hukum Islam/KHI) are two examples of Muslim family law where discrimination against women persist. This paper will discuss the problem of gender biases in the Islamic marriage law in Indonesia, the imperative of gender-sensitive law reform, and the implementation of the principle of maslaha as solution. It sheds lights on such biases and offer alternative perspectives, as these are advocated by Muslim reformers. This study argues that it is necessary to reform the Islamic marriage laws, which are gender sensitives, by removing discriminatory clauses. The reform is meant to realize maslaha (well-being/welfare) and is based on the implementation of the highest objective of Islamic law, formulated as maqāshid al-sharī‘a. These include preservation of religion (ḥifẓ al-dīn), mind (ḥifẓ al-‘aql), soul (ḥifẓ al-nafs), wealth (ḥifẓ al-mal), and descendants (ḥifẓ al-nasl).